Incidence of catastrophic healthcare expenditure and its main determinants in Mexican households caring for a person with a mental disorder - Lina Diaz-Castro; Héctor Cabello-Rangel; Carlos Pineda-Antúnez; Alejandra Pérez de León (Cambridge Prisms: Global Mental Health, 2021)
Abstract Background There are few studies on the impact of out-of-pocket mental health care expenditures and sociodemographic factors on the probability of Mexican households to incur catastrophic healthcare expenditures (CHE).